2019
DOI: 10.1002/ana.25406
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal tau accumulation and atrophy in aging and alzheimer disease

Abstract: Objective: To determine the rate of tau accumulation in healthy older adults (OA) and patients with Alzheimer disease (AD), as well as the relationship of tau accumulation to cortical atrophy. Methods: Two longitudinal flortaucipir (FTP) positron emission tomography (PET) and magnetic resonance imaging (MRI) scans were acquired from 42 OA (21 Pittsburg compound B [PiB] + , age = 77.6 AE 4.6 years, 25 female [F]/17 male [M]) and 19 PiB + patients with AD (age = 63.1 AE 10.3 years, 12 F/7 M) over 1 to 3 years of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
238
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(276 citation statements)
references
References 48 publications
33
238
4
1
Order By: Relevance
“…This interpretation is supported by the finding of a previous longitudinal tau PET study showing that amyloid1 individuals had steeper tau tracer retention increases in basal and midtemporal, retrosplenial, posterior cingulate, and entorhinal cortex [38]. Another study of longitudinal tau accumulation showed increases in 18 F-AV-1451 retention over 1-3 years in temporal and medial parietal areas in healthy older adults [39]. These findings were further expanded on by a recent study reporting that individuals with baseline 18 F-AV-1451 SUVRs in the second quartile exhibited tau tracer retention increases in inferior and lateral temporal cortex and in posterior cingulate over 18 months [15].…”
Section: Discussionsupporting
confidence: 58%
“…This interpretation is supported by the finding of a previous longitudinal tau PET study showing that amyloid1 individuals had steeper tau tracer retention increases in basal and midtemporal, retrosplenial, posterior cingulate, and entorhinal cortex [38]. Another study of longitudinal tau accumulation showed increases in 18 F-AV-1451 retention over 1-3 years in temporal and medial parietal areas in healthy older adults [39]. These findings were further expanded on by a recent study reporting that individuals with baseline 18 F-AV-1451 SUVRs in the second quartile exhibited tau tracer retention increases in inferior and lateral temporal cortex and in posterior cingulate over 18 months [15].…”
Section: Discussionsupporting
confidence: 58%
“…However, in many neurodegenerative disorders, brain atrophy is preceded and perhaps caused by the aggregation of pathological agents. In Alzheimer’s disease, the presence of tau is closely linked to [7, 8], and likely precedes [8, 11], gray matter atrophy. However, because gray matter degeneration observed in Alzheimer’s dementia may be caused by many sources other than Alzheimer’s pathology, gray matter degeneration itself cannot be used as proxy for tau (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Tau tangles are a pathological hallmark of AD, but they are neither specific to AD, nor to neurodegenerative disease in general. The process of aging appears to lead inevitably to the accumulation of tau tangles in the medial temporal lobe and occasionally beyond, a phenomenon known as primary age-related tauopathy (PART) [9], and in vivo evidence for the longitudinal accumulation of tangles in healthy elderly has been observed [11]. While PART may result in subtle insults to cognition and brain health [52], there is still debate as to whether PART and AD are distinct processes [53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross-sectional studies showed early tau deposition in cognitively healthy elderly (with or without significant A pathology) in temporal and medial parietal regions, most dominant in entorhinal and parahippocampal cortex, the amygdala and inferior temporal cortex. Longitudinal studies further suggest that cognitively healthy elderly accumulate tau in the medial temporal and medial parietal lobe, while (A positive) AD dementia patients increased in tau primarily in the frontal lobe (Harrison et al, 2018). The spread of tau beyond the MTL to the parietal lobe and other regions may be a critical milestone in the progression of AD.…”
Section: A Pet and Estimation Of Tfa+mentioning
confidence: 95%